2022
DOI: 10.4103/jfmpc.jfmpc_1647_21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of ‘AETCOM Module’ on the medical interns posted in peripheral health centres of a tertiary care medical college in Kanchipuram, Tamil Nadu

Abstract: Introduction: Effective communication skills between doctor and patient leads to enhanced patient satisfaction, better compliance to treatment and improved health outcomes. Aims and Objectives: To evaluate the effectiveness of Attitude, Ethics and Communication (AETCOM) module in improving the communication skills of the interns posted in peripheral health centres after methodical training and approach. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In this study, we have emphasized communication between doctor and patient. Jain et al [ 6 ] conducted a study on evaluating the effectiveness of ‘AETCOM Module’ on the medical interns posted in peripheral health centers of a tertiary care medical college in Kanchipuram, Tamil Nadu, and their reflective feedback has shown that most of the students expressed that they could identify the mistakes they commit while communicating with patients. The interns also expressed that the AETCOM classes would help them become better medical professionals and better doctors with a better understanding of patients' problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have emphasized communication between doctor and patient. Jain et al [ 6 ] conducted a study on evaluating the effectiveness of ‘AETCOM Module’ on the medical interns posted in peripheral health centers of a tertiary care medical college in Kanchipuram, Tamil Nadu, and their reflective feedback has shown that most of the students expressed that they could identify the mistakes they commit while communicating with patients. The interns also expressed that the AETCOM classes would help them become better medical professionals and better doctors with a better understanding of patients' problems.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] One such example is the experience of a medical college in Puducherry, where an Attitude, Ethics, and Communication (AETCOM) session was conducted on the topic of “Health Care as a Right.” The entire concept of the AETCOM module lies on the fundamental principle that changing a person's attitude can change his or her behavior, thereby improving the communication skills of the medical students, which in turn will prevent malpractices and litigations against doctors. [ 4 5 6 ] The assessment of AETCOM is preferably done in a real-world simulated scenario and not by written theoretical examinations. [ 7 ] The Department of Community Medicine developed a teaching model for AETCOM module 2.3, ‘Health Care As A Right,’ which is integrated with Community Medicine topics ‘Concept Of Health And Disease’ and ‘Healthcare Of The Community’.…”
Section: Introductionmentioning
confidence: 99%
“…By focusing on the AETCOM skills of medical students, institutions are trying to prepare their students capable of providing compassionate, patient-centered care that is respectful of cultural and social differences. [ 3 ] In addition, AETCOM helps to promote professionalism and ethical behavior among medical practitioners, which are essential for maintaining public trust in the healthcare system. However, as this is relatively a newly introduced component in the curriculum, both teachers are students are facing challenges in teaching–learning and assessment process.…”
Section: Introductionmentioning
confidence: 99%